Ethical regulation on researches at Brazil: do we need the 510 Resolution? (Revista Iberoamericana de Bioética, 2018)
Since 1996, with the implementation of the 196/96 National Health Council Resolution, Brazil has risen on the world stage as an important country with regard the regulatory aspect of research with human beings. New challenges, amendments and complements lead to a new Resolution, the 466/12. Since the implementation of 196/96 through to the present day with the 466/12, some groups of researchers in Social and Human Sciences displayed dissatisfaction with the Brazilian regulatory system and they proposed a new Resolution specific to research in the field of Social and Human Sciences. Thus, Resolution 510/16 was created. This article discusses if this Resolution is necessary.
Keywords: ethical analysis; ethical review; ethics; research